Temporal control of protein labeling by a photo-caged benzaldehyde motif and discovery of host cell factors of avian influenza virus infection. Issue 67 (4th August 2022) - Asiimwe, Nicholas; Lee, Jung Hoon; Hong, Kyung Tae; Murale, Dhiraj P.; Haque, Md. Mamunul; Kim, Dong-Hoon; Lee, Jun-Seok
Abstract : Photo-caged benzaldehyde probes using o -nitrophenylethylene glycol were designed for photo-activated electrophile generation. Abstract : Photo-caged benzaldehyde probes using o -nitrophenylethylene glycol were designed for photo-activated electrophile generation. Using photo-activated electrophile generating probes, we successfully revealed under-represented host cell response factors using an avian influenza virus infection model.